Information System Agility And Covid-19: An Exploratory Model to Minimze Pandmeics Effects On Small and Medium Enrprises (Global Journal of Management and Business Research, 2024)
Over the past few years many small and medium enterprises SMEs have adopted agile information systems IS as they try to adapt to the uncertainties of the COVID-19 pandemic that not only resulted in many deaths but also disrupted the markets for the products and services of most SMEs The aim of this research is to propose an exploratory model to explain the relationship between consumers SMEs and agile information systems and how they influence decision-making and financial decisions during and after the COVID-19 pandemic The researchers employed qualitative methods as the research strategy for this study and supplemented their findings with quantitative approaches applied to a brief case study The independent variables intelligence flexibility awareness and competencies have a significant effect on the dependent variable information system agility R2 for the independent variables is 0 and R2 for the dependent variable is 0 66 consequently the hypotheses of the research are statistically accepted An exploratory model was created based on the theoretical background and statistical analysis of the obtained data
Keywords: agility; COVID-19; information system; dynamic capabilities